Policy Direction for Development of Islamic College Library in Indonesia - Rodin, Rhoni (Department Library of Governance Institut of Home Affairs, 2022)
Problem Statement: Islamic college library is expected to change and remain updated in facing global challenges. Purpose: This research aimed to analyze the policy direction of the development of Islamic college library in Indonesia. Method: This was literature research from various sources, journals, books, documentation, and the internet. Furthermore, a descriptive analysis method was used in analyzing the data. Result: The results showed that the Islamic college library faced some problems. First, traditional roles should not be prioritized by providing physical facilities. Second, the Islamic college library should also be prepared for user behavior changes that have occurred with rapid technology advancements. Third, aspects of the college mission, namely developing and advancing research, should be improved. Fourth, the open access movement is also a challenge to consider. In addition to facing various management problems, the library should also prepare a policy direction and grand design for the development of Islamic colleges in the face of the future era. Conclusion: In conclusion, the policy direction and grand design refer to the components of the library accreditation issued by the National Library Standards Agency for Higher Education. Keywords: policy direction, Islamic college library, Indonesia